The research of left-handed Coplanar-waveguide transmission line - Jia-hui Fu; Qun Wu; Wei Pan; De-Fu Wang (2009 Asia Pacific Microwave Conference, 2009)
Using coplanar waveguide (CPW) to construct left-handed(LH) transmission line is more effective method than microstrip line. In this paper, a new type of LH transmission-line is proposed. It is composed with parallel embedded inductive and serial interdigital capacitor. Through extracting ß parameter of CPW transmission line, the region of LH transmission-line is obtained from 6 GHz to 14 GHz. The effective bandwidth is about 52% in 7.5 GHz-12.7 GHz. The backward-wave characteristic is validated by full-wave simulation.